Ensinando Percepção Musical: um estudo de caso na disciplina do curso técnico de um Instituto Federal de Educação, Ciência e Tecnologia - Horn, Suelena de Araujo Borges (2016)
In this study, we addressed music perception under the perspective of Music Education, with the general objective of understanding how teaching works in the Music Perception discipline of a technical degree course in Musical Instrument, held out by a Brazilian Federal Institute of Education, Science and Technology. Conducting a case study, based on data collection techniques such as documentation review, observation and interview, we analyzed the pedagogical project of the course, in order to understand Music Perception discipline structure, functions and objectives. Through the observations made during the span of 12 weekly classes, it was possible to obtain data on the pedagogical practice of the discipline professor, as well as his didactical procedures, materials, methodologies and ways of interacting with students. On the other hand, the interview given by the professor allowed us to know his academic background and conceptions, pointing to underlying aspects of his pedagogical practice. The literature review comprised themes of music perception and professional education, considering research in Education and Music Education areas. We noticed two trends in the teaching of music perception: one guided by a model based on traditional music teaching (marked by strict ear training, fragmented approach on the music elements and a gap between teaching and students’ musical practices) and another one that covers a variety of proposals that intend to renew teaching strategies in music perception (based on students’ musical practices, regarding both repertoire and didactical strategies, as well as an integrated approach of music elements). We also identified the presence of a conflict between the strictness of the traditional model and the necessity of pedagogical practices that take compromise with students’ realities, as suggested by the representations on education present in Music Education field and in the professional education documents. Finding the opposition between trends, we explored Bourdieusian concepts and analyzed the possibility to establish orthodox and heterodox positons inside a field. We understood that the practices found in the teaching of music perception are influenced by a set of dispositions embodied in their agents, deriving from representations present in the artistic-musical field. Such dispositions generate an educational model that is based on values and beliefs related to music conservatories, which were traditionally adopted on the professional musician education, creating what is called habitus conservatorial. According to Perrenoud, the pedagogical practice construction is based on habitus and, therefore, a reflexive practice in the act of teaching is recommended, so that the professor’s procedures overcome the reproduction of educational models. Through analysis of the gathered data, we identified that teaching in the studied case is influenced by the conflicts present in the music education field, marked by practices bound to an habitus conservatorial and permeated by ambiguous conceptions from both artistic-musical and educative fields.